(Re-)Designing institutions for EMU wage setting: Strengthened coordination between Monetary and Economic Institutions. Issue 4 (December 2017) - Dahan¹, Samuel
This article uses the concept of 'institutional learning' to make a legal case for a stronger wage policy at the EMU level. This article takes the view that an inherent asymmetry in the EMU, namely the presence of a unified monetary policy without a commensurate coordination of wage-setting mechanisms, contributed to the development of the crisis. The latent consequences of this flaw—diverging (wage) growth and cost competitiveness—were brought into full view when the global financial crisis struck. A unique wage-coordination process has already become institutionalised at the EU level through the European Semester: wage and spending cuts supplant the role of currency depreciation as a means of addressing external economic shocks and competitiveness gaps. We argue that the new wage coordination process constitutes a step in the right direction insofar as the EU has learned from its mistake, namely creating a currency union without any transnational wage determination mechanism. However, this paper makes a legal and institutional case for a more reflexive and solidaristic approach to wage coordination. In order to do so, we take the economic view that stronger EU labour coordination is not likely to diminish competitiveness. While market wisdom would seem to support the view that decentralised collective bargaining systems performs better, evidence suggests that solidaristic wage-setting offers a critical means of channelling economic policy into a model less narrowly focused on labour cost. Beyond the economic debate, there is a legal case to be made in favour of stronger wage bargaining that can reconcile the markets with labour law in the EMU. It is the role of lawyers to investigate possible legal avenues towards achieving a more appropriate solution that is compatible with the Treaty of Lisbon as well as with the goal of competitiveness. Our project does not advocate Treaty changes; instead we use the concept of 'institutional layering/learning' to reinforce already-existing reflexive approaches such as the Macroeconomic Dialogue (MED) in order to create a multi-level wage determination strategy that mediates a genuine facilitation process between the Commission, the European Central Bank and the unions.